Smoking under the tsars : a history of tobacco in imperial Russia - Starks, Tricia, 1969- (Cornell University Press, 2018)
"Using unusual sources and approaching tobacco from the perspective of users, producers, and objectors, this monograph provides a view of the early transfer by the Russian market to smoking and presents the addictive, nicotine-soaked Russian cigarette - the papirosa - and the sensory, medical, social, cultural, and gendered consequences of this unique style of tobacco use"--